Mandarin For Career: Pelatihan Bahasa Mandarin Dasar untuk Fresh Graduate Ekonomi Pembangunan Memasuki Dunia Kerja Global - Muhammad Mufti Hudani; Sobita, Nindya Eka; Rizka Malia; Mega Mariska (Jurnal Pengabdian Masyarakat, 2026)
This community service initiative was motivated by the rapid growth of Chinese investment in Lampung Province, which has generated new job opportunities in the financial services sector. However, this development has not been matched by the availability of human resources with basic Mandarin language skills. Responding to this need, a team of lecturers from the Faculty of Economics and Business, University of Lampung, in collaboration with PT Maybank Sekuritas Indonesia, Lampung Branch, organized a Mandarin for Career training program for students and alumni of the Development Economics Department. The training was conducted through a one day in-person workshop followed by two weeks of online mentoring. The program covered theoretical foundations, practical conversation exercises, CV preparation, and mock job interviews in Mandarin. Evaluation was carried out using a pre-test, post-test, and participant reflections. The results show a substantial improvement in participants’ abilities, with the average score rising from 39 to 79. A total of 85% of participants were able to introduce themselves in Mandarin, and 70% could engage in simple workplace-related conversations. Beyond language competence, this activity also strengthened collaboration between the university and the industry while creating a talent pool of job-ready graduates. The training proved effective in enhancing graduates’ competitiveness and supporting regional economic resilience in an increasingly globalized era.